(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the quality of life of the directors of kindergartens, and the basic research sample consisted of (384) principals and assistants, who were chosen by simple random method from the directorates of Baghdad Education (Al-Rusafa First, Rusafa Second, Third Rusafa, First Karkh, Second Karkh Third Karkh) for the academic year (2021/2022). the researcher translated the quality of life scale for " Swamy and his colleagues, 2015", then analyzed the paragraphs of the scale logically and statistically to calculate their discriminatory ability and their validity coefficients. Stability (0.99, 0.98) respectively, so that the quality of life measure consists of (48) items, and in front of each paragraph there are five alternatives (I always agree, sometimes agree, do not agree, sometimes do not agree, and do not always agree), and the two scales were applied at the same time On the final application sample. Based on the sample responses, the following conclusions were reached: . The level of quality of life for kindergarten principals is high, as the results came with an arithmetic mean higher than the hypothetical mean of the scale.